Assessing and treating victims of violence - Briere, John. (San Francisco : Jossey-Bass, 1994)
Recent research has shown that a significant proportion of North American children are sexually, physically, or psychologically abused each year, and that the number of reports of adult rape, spousal abuse, and physical assault by strangers continues to grow. Beyond the epidemiology of societal violence per se is its impact on the mental health of those who live in our culture.
Scientists and clinicians are beginning to trace the genesis of a number of psychological symptoms and disorders to childhood or adult traumatic events, many of which involve interpersonal violence. As a result, a new specialty of mental health practitioners has evolved, one specifically concerned with the assessment and treatment of psychological trauma. At the same time, however, the typical front-line clinician is bound to encounter children and adults who have been victimized and who present with complex post-traumatic sequelae. It is for the trauma specialist and the general clinician that this issue of New Directions for Mental Health Services was developed.
Although the subject matter of this issue is disturbing, growing assessment and treatment technology gives us new hope for treating victims of violence.
Editor's Notes / John Briere -- 1. Assessing Adult Victims of Interpersonal Violence / Diana M. Elliott -- 2. Assessing Children for the Effects of Sexual Victimization / William N. Friedrich -- 3. Long-Term Correlates of Childhood Sexual Abuse in Adult Survivors / Debra A. Neumann -- 4. Posttraumatic Stress Disorder in Victimization-Related Traumata / Millie C. Astin, Christopher M. Layne, Angela J. Camilleri and David W. Foy -- 5. Treating Child Victims of Sexual Abuse / Cheryl B. Lanktree -- 6. Treatment of Adult Victims of Rape / Barbara J. Gilbert -- 7. Assessing and Treating Battered Women: A Clinical Review of Issues and Approaches / Beth Houskamp -- 8. Treating Survivors of Child Sexual Abuse: A Strategy for Reintegration / Karin C. Meiselman.
Includes bibliographical references and indexes.
Keywords: Sexual abuse victims -- Rehabilitation; Sexual abuse victims -- Mental health; Victims of crimes -- Rehabilitation; Victims of crimes -- Mental health